2012
DOI: 10.1111/j.1463-1318.2011.02548.x
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal function evaluation and predictive factors for faecal incontinence in 600 patients

Abstract: Incontinent patients have lower pressures, smaller rectal capacity and more sphincter defects than controls, but show a large overlap. Our model shows a relatively high sensitivity and negative predictive value for predicting FI in women. The model seems promising in the patients studied with a temporary stoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 47 publications
1
24
2
3
Order By: Relevance
“…They concluded that anorectal physiology testing is useful in the evaluation of patients with FI with transanal ultrasonography being the most likely to change their management [15]. Overall, the results of physiology testing have yet to be consistently correlated with prediction of outcomes following various treatments for FI [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that anorectal physiology testing is useful in the evaluation of patients with FI with transanal ultrasonography being the most likely to change their management [15]. Overall, the results of physiology testing have yet to be consistently correlated with prediction of outcomes following various treatments for FI [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The work-up of patients with FI often includes anorectal physiology testing and transanal ultrasonography [12]. Though the goals of these testing modalities are to correlate objective findings with selection for particular treatment modalities, data from these studies have not been consistently shown to correlate with the severity of FI or prediction of outcomes following treatment with traditional management algorithms [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lam et al konnten in einer aktuellen Studie eindrücklich belegen, dass beide diagnostischen Verfahren keine wirkliche Korrelation mit klinischen Inkontinenzsymptomen bzw. deren Schweregraden hatten [8]. Im Rahmen der Studie wurde dargestellt, dass inkontinente Frauen häufiger an chronischer Diarrhoe litten, manometrisch niedrigere Ruhe-und Kneifdrücke sowie eine verminderte rektale Kapazität bzw.…”
unclassified
“…Im Rahmen der Studie wurde dargestellt, dass inkontinente Frauen häufiger an chronischer Diarrhoe litten, manometrisch niedrigere Ruhe-und Kneifdrücke sowie eine verminderte rektale Kapazität bzw. Compliance aufwiesen und häufiger endosonografisch nachweisbare Sphinkterdefekte vorlagen; hingegen waren bei stuhlinkontinenten Männern nur die manometrisch reduzierten Drücke im Vergleich zu kontinenten Patienten nachweisbar [8]. Die klinischen Ausprägungsformen der Stuhlinkontinenz müssen zusätzlich von der Stuhlentleerungsstörung differenziert werden -und dies ist im klinischen Alltag nicht selten schwierig, da hier bei vielen weiblichen Patienten ein "overlap" besteht -insbesondere das Symptom "wiederholte Defäkation" wird subjektiv als Stuhlinkontinenz empfunden, während klinisch eher eine Entleerungsstörung vorliegt.…”
unclassified